Reflexing interfaces the complex coevolution of information technology ecosystems - Orsucci, Franco; Sala, Nicoletta (Gale virtual reference library, 2008)
Discusses the application of complex theories in information and communication technology, with a focus on the interaction between living systems and information technologies, providing researchers, scholars, and IT professionals with a fundamental resource on such topics as virtual reality; fuzzy logic systems; and complexity science in artificial intelligence, evolutionary computation, neural networks, and 3-D modeling.